Line by line [large type] - Delamere, Jennifer (Delamere, Jennifer. Love along the wires, 2020)
"Alice McNeil resolved to travel through life unencumbered by love or marriage, free to make her own decisions. She's recently acquired a position at an important trading firm, but when the company's ambitious junior director returns to London, things change in ways Alice could never have imagined. For Douglas Shaw, years of hard work and ingenuity enabled him to escape a life of grinding poverty. He's also determined to marry into high society--to ensure he never returns to the conditions of his past. When Alice and Douglas are forced to confront what is truly important in their lives, will their growing bond give them the courage to risk finding a better way?"--Back cover.